Antifrosting Performance of a Superhydrophobic Surface by Optimizing the Surface Morphology - Jiang, Shuyue; Zhang, Haifeng; Jiang, Chunfeng; Liu, Xiaowei (Langmuir, 2020)
Improving the antifrosting ability of stainless steel is crucial. In previous reports, many efforts have been dedicated to enhancing the antifrosting performance of superhydrophobic surface by fabricating different surface morphology. However, no researchers have proposed what kind of surface morphology can effectively prevent the frost based on the theory of superhydrophobic surfaces. In this article, we build a simulation model to study the effects of different surface morphology on antifrosting based on the Cassie model. We find that the higher the proportion of air between the droplet and the substrate, the better the antifrosting performance of the superhydrophobic surface. Therefore, we propose one superhydrophobic surface (denoted as sample #R) fabricated by selective growth. It can contain more air between the droplet and the surface. Further frosting experiments at a low temperature of −21 °C and a humidity of 75% show that 15% frost coverage on sample #R can be delayed to 63 h, as compared to less than 3 h for untreated stainless steel. In addition, the preparation method is generally applicable to other metals. Therefore, this work provides new insights into the rational design of a superhydrophobic surface with antifrosting in a harsh environment.